(untitled) (Bangladesh Journal of Urology, 2020)
Introduction and Objective: Laparoscopic surgery is increasingly exercised in urology due to improvements in technical capabilities and experience. It comes with many advantages compared to open surgery such as lesser degree of pain and haemorrhage, shorter hospital stay and better cosmetic results. This study is carried out to evaluate the outcomes and complications of urological laparoscopic surgery cases performed Chittagong Medical College Hospital, Chattogram, Bangladesh. Methods: This was a hospital based prospective observational study of total 29 patients, who received laparoscopic surgery of different kinds between January 2017 and September 2019 for urological causes with a minimum one month follow-up. Included patients were assessed in terms of demographic characteristics, preoperative diagnosis, type of laparoscopic approach, duration of surgery and hospitalization, complications after surgery and need for conversion to open surgery. Results: The mean age was 45.03 years where 12 patients were women and 17 were male. All patients underwent trans-peritoneal procedures where2 patients received renal cyst excision, 4 simple nephrectomy, 5 ureterolithotomy, 9 radical nephrectomy, 1 radical cystectomy, 2 adrenalectomy, 3 pyelolithotomy and 3 pyeloplasty. Three of the 29 patients required conversion to open surgery. Except these patients, no major complication or mortality was encountered. The mean duration of surgery for the most commonly applied procedures were as follows: renal cyst excision 87.5 (70-105) min, simple nephrectomy 141.25 (120-170) min, ureterolithotomy 120 (100-140) min, radical nephrectomy 215.56 (180-260) min, pyelolithotomy 120 (100-140) min, and pyeloplasty 156.67 (130-190) min. The mean hospital stay was 4.59±1.7 (2-8) days. Conclusions: The success and complications rate of the laparoscopic urological surgeries performed in our hospital were consistent with those reported in the literature. In the light of technological advances and increasing experience, we believe that laparoscopic surgery is an effective technique with excellent outcome along with a safe and feasible alternative to open surgery in the field of urology. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.17-23